2018
DOI: 10.3389/fnins.2018.00276
|View full text |Cite|
|
Sign up to set email alerts
|

Lateral Symmetry of Synergies in Lower Limb Muscles of Acute Post-stroke Patients After Robotic Intervention

Abstract: Gait disturbance is commonly associated with stroke, which is a serious neurological disease. With current technology, various exoskeletons have been developed to provide therapy, leading to many studies evaluating the use of such exoskeletons as an intervention tool. Although these studies report improvements in patients who had undergone robotic intervention, they are usually reported with clinical assessment, which are unable to characterize how muscle activations change in patients after robotic interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 36 publications
1
61
0
1
Order By: Relevance
“…A voluntary drive is essential to achieve a desired behavior in robot-assisted motor learning (Lotze, 2003). The HAL system provides motion support tailored to the wearer's voluntary drive (Kawamoto et al, 2013), and it has been shown that the walking performance in patients wearing HAL approximates that of healthy people using HAL (Puentes et al, 2018;Tan et al, 2018). A single-leg version of HAL can give active and intensive support to the gait pattern when rehabilitating a patient after acute stroke (Nilsson et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A voluntary drive is essential to achieve a desired behavior in robot-assisted motor learning (Lotze, 2003). The HAL system provides motion support tailored to the wearer's voluntary drive (Kawamoto et al, 2013), and it has been shown that the walking performance in patients wearing HAL approximates that of healthy people using HAL (Puentes et al, 2018;Tan et al, 2018). A single-leg version of HAL can give active and intensive support to the gait pattern when rehabilitating a patient after acute stroke (Nilsson et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in another study evaluating longitudinal changes in modular motor coordination during locomotion in subacute stroke survivors, no substantial changes in the number of motor synergies were found after 1 month of conventional therapy [24]. Finally, in the most recent study on subacute stroke survivors an increased lateral symmetry in muscle synergies while walking, associated with improvements in gait kinematics measurements, was found after 3 weeks of walking training supported by a lower limb exoskeleton [25]. Overall, it remains uncertain whether a rehabilitation treatment can alter motor coordination as measured by muscle synergies and how much this alteration is associated with motor recovery after stroke.…”
Section: Introductionmentioning
confidence: 90%
“…Few studies explored the changes of muscle synergies after a rehabilitative intervention [20][21][22][23][24][25]. Two of them were focused on upper limb motor recovery in chronic stroke patients [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to studies with patients with SCI, studies with post-stroke patients assessed the gait performance, without wearing exoskeleton, after training with the exoskeleton and compared the results with the baseline measurements. In general, we found that the degree of mobility improvement was not as substantial as with the studies focusing on SCI patients: 12 out of 16 studies analyzing gait speed reported an improvement [37,47,87,102,[105][106][107][108][109][110][111][112], and only 3 out of 9 studies analyzing Flugl-Meyer scores reported an improvement [102,109,112]. Regarding the group of studies focusing on other pathologies, 4 out of 7 studies analyzing outcome measures related to gait speed reported an improvement [36,86,113,114].…”
Section: Performance Assessmentmentioning
confidence: 96%